2016
DOI: 10.1093/abbs/gmw047
|View full text |Cite
|
Sign up to set email alerts
|

Factors forming the BRCA1-A complex orchestrate BRCA1 recruitment to the sites of DNA damage

Abstract: Sustaining genomic integrity is essential for preventing onset of cancers. Therefore, human cells evolve to have refined biological pathways to defend genetic materials from various genomic insults. DNA damage response and DNA repair pathways essential for genome maintenance are accomplished by cooperative executions of multiple factors including breast cancer type 1 susceptibility protein (BRCA1). BRCA1 is initially identified as an altered gene in the hereditary breast cancer patients. Since then, tremendous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 83 publications
0
33
0
5
Order By: Relevance
“…It also has a high MAF in the population databases (0.12 [42] and 0.24 [62]). Together with Abraxas, RAP80 is part of the BRCA1-A complex which is important for recruiting BRCA1 to double-strand break (DSB) sites [63] and studies have shown that truncating variants in both proteins are associated with increased irradiation sensitivity, deficient BRCA1 recruitment to DSB sites and genomic instability [64][65][66][67]. Three patients that carried only these two variants were evaluated for BRCA1/BRCA2 CNVs and all tested negative.…”
Section: Discussionmentioning
confidence: 99%
“…It also has a high MAF in the population databases (0.12 [42] and 0.24 [62]). Together with Abraxas, RAP80 is part of the BRCA1-A complex which is important for recruiting BRCA1 to double-strand break (DSB) sites [63] and studies have shown that truncating variants in both proteins are associated with increased irradiation sensitivity, deficient BRCA1 recruitment to DSB sites and genomic instability [64][65][66][67]. Three patients that carried only these two variants were evaluated for BRCA1/BRCA2 CNVs and all tested negative.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the PARsylated region of BRCA1 does not resemble any of the known PAR-containing modules, such as the PBZ, WWE, FHA, OB-fold, RRM, and PIN domains (43), suggesting that it might operate differently, at least in part. In this regard, others have reported that the BRCT domains of the major BRCA1 partner, BARD1, can bind poly-ADP-ribose, which facilitates the early recruitment of BRCA1/BARD1 heterodimers to DSBs (10,40).…”
Section: Brca1 Overexpression Is Associated With Aneuploidy and Poormentioning
confidence: 99%
“…BRCA1 is a major HRR support protein (10,11). Working together with certain partner proteins, including RAD51, CtIP, and BACH1 (also known as FANCJ/BRIP1), it promotes doublestrand break (DSB) end resection, proper HRR progression, and recombinational fidelity (12)(13)(14).…”
mentioning
confidence: 99%
“…BRCA2-CONTAINING COMPLEX 36 HOMOLOG A (BRCC36A) and BRCC36B are two other JAMM proteases in Arabidopsis, which display high sequence similarity to the mammalian BRCC36 that is involved in the DNA damage response pathway as subunit of the BRCA1-A complex, one of the most characterised complex involved in tumour suppression in humans ( Her et al, 2016 ). BRCC36A/B are expressed ubiquitously and neither the single mutants nor the brcc36a/b double mutant shows any developmental problems.…”
Section: Jamm Family: Components and Molecular Activitiesmentioning
confidence: 99%